Yield of peperina (Minthostachys mollis (Kunth.) Griseb.) populations in the year following planting: response to cropping regimen - Ojeda, M.=700 1 Arroyo, A.; Borgogno, P.; Biderbost, E.; Balzarini, M.
(Es, En)
ilus., 11 ref.
Keywords: CULTIVO; MINTHOSTACHYS; PLANTAS AROMATICAS; CONTENIDO DE MATERIA SECA; ACEITES ESENCIALES; ARGENTINA; PEPERINA; MINTHOSTACHYS MOLLIS